Caterpillar Inc. equity research report - Alfani, Leonardo (2024)
The following paper will perform an equity valuation analysis of the company Caterpillar Inc. contextualized in its main operating sectors. The analysis will be carried out using a DCF model to reach a final equity value per share with the objective of comparing this obtained value with the present market price of the company’s shares. The paper will so develop: the Introduction will address the importance of valuation and then present the company being valued. To follow, a literature review will be presented, showing the fundamentals and the theorical bases sustaining the soundness of a valuation methodology like the DCF model. The Valuation section applies the elements presented in the literature review section in order to reach a fair value for Caterpillar. The Conclusions and General Discussions section closes the analysis. Here a comparison with the equity report from Morningstar and a recommendation with regard to Caterpillar Inc. will be made. The report and the collection of data has been concluded on the day of the issue of Caterpillar’s annual report, February the 16th 2024.